Racial microaggression in academic setting: A focus on University students (findings). - Lino, Mitshel (Universiti Sains Malaysia, 2014)
Currently in Malaysia, the traditional, direct and overt racism might be nearly non-existent owing to the enactment of anti-discriminative law and introduction of 1Malaysia policy “harmony and unity in diversity”. However, traditional racism has been replaced by racial microaggression – the contemporary, indirect and subtle form often performed by modern and educated population